Principles of Educational Technologies and Modular Education in the Introduction of A Dynamic Model of the System of Training Primary Education Masters - Yuldashev Rustam Elmurodovich (Genius Journals, 2022)
The article analyzes the experience of educational technologies and modular teaching principles, which are part of the structural components of the dynamic model of the system for preparing masters of primary education
Keywords: Implicit; dynamics; education; profession